Sign in to follow this  
RoundBear

Macroeconomics help please

7 posts in this topic

I was wondering can anyone show step by step how this is done

Determine whether constant, decreasing, or increasing returns to scale

1) F(K,L) = K^2/L

2) F(K,L) = K+L

3) F(K,L)= square root of K+ square root of L

4) F(K,L)= K^2+L^2

Fg will be given to anyone who gives a clear step by step.

Share this post


Link to post
Share on other sites

You just have to compare aF(K,L) with F(aK,aL) where a is a constant greater than 1.

If aF(K,L) = F(aK,aL) it is constant EDIT: in the constant case a >=0

If aF(K,L) > F(aK,aL) it is decreasing

If aF(K,L) < F(aK,aL) it is increasing

1) F(K,L) = K^2/L

F(aK,aL) = a^2 K^2/aL = aK^2/L

aF(K,L) = aK^2/L

Constant

2) F(K,L) = K+L

F(aK,aL)= a + K + a + L = 2a + K + L

aF(K,L) = a(K+L)

Pretty sure this is decreasing

3) F(K,L)= square root of K+ square root of L

F(aK,aL)= root aK + root aL = roota (rootk + rootl)

aF(K,L) = a(rootK+rootL)

Decreasing

4) F(K,L)= K^2+L^2

F(aK,aL)= a^2 K^2 + a^2 L^2 = a^2(K^2+L^2)

aF(K,L) = a(K^2+L^2)

Increasing.

Pretty sure I remembered this correctly. Hope it helps!

Share this post


Link to post
Share on other sites

I still dont get it lol.

Why is #2 decreasing?

2) F(K,L) = K+L

F(aK,aL)= a + K + a + L = 2a + K + L

aF(K,L) = a(K+L)

I thought you only put the constant a in front of the K and L. So it'll be like F(K,L) = aK+aL

hmm would it be better if i just substituted a value for K, L, and a? and then I can just add them up and compare the original F(K,L) to the new F(K2,L2)?

Share this post


Link to post
Share on other sites
I still dont get it lol.

Why is #2 decreasing?

2) F(K,L) = K+L

F(aK,aL)= a + K + a + L = 2a + K + L

aF(K,L) = a(K+L)

I thought you only put the constant a in front of the K and L. So it'll be like F(K,L) = aK+aL

hmm would it be better if i just substituted a value for K, L, and a? and then I can just add them up and compare the original F(K,L) to the new F(K2,L2)?

I don't understand what you're saying, but I believe it is decreasing because aF(K,L) is multiplicative as opposed to being additive and a > 1 so that function will eventually dominate and be the upper function.

Share this post


Link to post
Share on other sites

Create an account or sign in to comment

You need to be a member in order to leave a comment

Create an account

Sign up for a new account in our community. It's easy!

Register a new account

Sign in

Already have an account? Sign in here.

Sign In Now

Sign in to follow this